2002
DOI: 10.1021/jm010539n
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Furamidine Analogues in Tumor Cells:  Influence of the Number of Positive Charges

Abstract: Fluorescence microscopy has been used to study the cellular distribution properties of a series of DNA binding cationic compounds related to the potent antiparasitic drug furamidine (DB75). The compounds tested bear a diphenylfuran or a phenylfuranbenzimidazole unfused aromatic core substituted with one or two amidine or imidazoline groups. The synthesis of five new compounds is reported. The B16 melanoma cell line was used to compare the capacities of mono-, bis-, and tetracations to enter the cell and nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 28 publications
1
77
0
Order By: Relevance
“…Defining new nucleic acid targets is thus a very promising route for expanding useful drug design approaches. Diamidines have excellent transport properties into a variety of cells [3][4][5][6] and an orally available prodrug of the diamidine, DB75, furamidine (Figure 1), is currently in phase III clinical trials against trypanosomes, which cause sleeping sickness, as well as other microbial parasites. 4,[7][8][9][10][11] DB75 binds strongly in the minor groove of DNA and recognizes sequences of at least four AT base pairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining new nucleic acid targets is thus a very promising route for expanding useful drug design approaches. Diamidines have excellent transport properties into a variety of cells [3][4][5][6] and an orally available prodrug of the diamidine, DB75, furamidine (Figure 1), is currently in phase III clinical trials against trypanosomes, which cause sleeping sickness, as well as other microbial parasites. 4,[7][8][9][10][11] DB75 binds strongly in the minor groove of DNA and recognizes sequences of at least four AT base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Diamidines have excellent transport properties into a variety of cells [3][4][5][6] and an orally available prodrug of the diamidine, DB75, furamidine (Figure 1), is currently in phase III clinical trials against trypanosomes, which cause sleeping sickness, as well as other microbial parasites. 4,[7][8][9][10][11] DB75 binds strongly in the minor groove of DNA and recognizes sequences of at least four AT base pairs. [7][8][9] For design of new agents that target additional disease organisms/cells as well as evading any possible resistance that could develop, we have focused on modifications of the structure, heterocycles, and properties of the basic units of the DB75 molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[22,33] Furthermore, it was previously shown that positively charged terminal groups are responsible for accumulation into cells. [34,35] Here presented pairs of acyclic and cyclic amidine derivatives have shown almost identical activities against all examined bacterial species. The lipophilic character of compounds has been found to be important parameter for the observed activity of the tested benzoimidazole derivatives against Moraxella catarrhalis.…”
Section: In Silico Analysis Antibacterial Activity and Structure Actmentioning
confidence: 78%
“…32 In general, these molecules should have a minimum two cationic groups to show significant binding and biological activity. Due to the high pK values of the amine moieties and low solubility of the compounds, the number of protons per molecule present in compounds 5a-h and the corresponding pK values could not be determined by standard potentiometric pH titration.…”
Section: Chemistrymentioning
confidence: 99%